Pandemics and their geographical distribution - N. Komilova; N. Mukhammedova; N. Ermatova; Z. Ibragimova; S. Bafoeva (Медицина неотложных состояний, 2023)
Background. The relevance of the presented article is due to an increase in the incidence of COVID-19 and the pandemic getting out of control. In the current conditions, the experience of previous generations and ancient pandemics will be useful for further study of the situation. The purpose of the article is to compare and analyze the experience of overcoming and passing through pandemic states and periods in the history of mankind, as well as to draw up possible theoretical methods for influencing the current situation through this experience. Materials and methods. To reveal the topic, authors used the methods of comparative analysis, historical perspective, induction and deduction, as well as an appeal to archival sources and international authors. Results. Thanks to the derived statistics of the incidence of coronavirus, preventive measures have been created against the spread of the pandemic, the use of which in the future will significantly reduce the risks of morbidity. Conclusions. In the field of studying COVID-19, the experience of previous epidemic periods of history has not been applied on a global scale, which determines the novelty of the presented article.